Epiphytic Orchid Diversity along an Altitudinal Gradient in Central Nepal - Timsina, Binu; Kindlmann, Pavel; Subedi, Sajan; Khatri, Subhash; Rokaya, Maan B (Plants (Basel, Switzerland), 2021)
Epiphytic orchids are common in subtropical forests, but little is known about the factors that determine their diversity. We surveyed two sites (north-facing Phulchowki and south-facing Shivapuri hills), in the sub-tropical forest in the Kathmandu valley, central Nepal. Along five transects per site, spanning an altitudinal gradient of 1525-2606 m a.s.l., we recorded all epiphytic orchids and the host species on which they were growing. The data were analyzed using a generalized linear model (GLM) and redundancy analysis (RDA). Species richness significantly decreased with increasing altitude and was higher in larger hosts and in places with high temperature. Species composition was affected by altitude, distance from the forest edge, host type, and precipitation. This study indicates that the most important factors affecting epiphytic orchid diversity was altitude, even if other factors were associated with patterns in composition. The low-altitude habitats with high species diversity are the best places for epiphytic orchids in this region. The altitudinal species richness and patterns in composition revealed by this study provide a baseline for further studies on epiphytic orchids.
Keywords: host; environmental factors; diversity pattern; Orchidaceae; ecology